First records of Xylosandrus compactus (Coleoptera: Curculionidae, Scolytinae) in the Iberian Peninsula: an expanding alien species? - Riba-Flinch, Josep M; Leza, Mar; Gallego, Diego (Zootaxa, 2021)
Xylosandrus compactus (Eichhoff) (Col.: Curculionidae, Scolytinae) is an ambrosia beetle species native to subtropical Eastern Asia, with great concern due to its high invasive ability. This species has invaded 54 countries worldwide, including 4 European countries (Italy, France, Greece, and Spain); it was detected in Mallorca (Balearic Islands, Spain) in October 2019. In the present work, X. compactus is recorded for the first time in the Iberian Peninsula (Girona province, NE Spain); specimens were collected in Banyoles (August 2020, attacking twigs of Laurus nobilis and Liquidambar styraciflua) and Platja d’Aro (October 2020, attacking twigs of L. nobilis). Up-to-date information is presented about its geographical distribution, host plants, biology, symptoms, associate damages, and the possible origin of this species in Europe.